An efficient multi-component synthesis of N-1-alkylated 5-nitrouracils from α-amino acids. Issue 22 (1st June 2016) - Boiteau, Jean-Guy; Bouix-Peter, Claire; Chambon, Sandrine; Clary, Laurence; Daver, Sebastien; Dumais, Laurence; Fournier, Jean-François; Harris, Craig S.; Mebrouk, Kenny; Millois, Corinne; Pierre, Romain; Rodeville, Nicolas; et al.
Graphical abstract: Highlights: An efficient route to N -1-alkylated 5-nitrouracils from α-amino acids is disclosed. From a large reaction conditions' screen Cs2 CO3 was identified as the optimal base. In situ epimerisation during the cyclocondensation step is also controlled. Abstract: The preparation of N -1 selectively alkylated uracil intermediates usually requires selective protection at N -3 followed by alkylation at N -1 and subsequent removal of the protecting group. In this Letter, we show the limitations of this approach when quaternary C centres at N -1 became a key target for the programme. To access this key substructure, we developed an efficient multi-component reaction (MCR) from readily available α-amino acid precursors.